2016
DOI: 10.1021/acs.jafc.6b01208
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycemic Constituents Isolated from Trapa natans L. Pericarps

Abstract: Trapa natans L., called water chestnut or water caltrop, is a floating aquarium plant. Its fruits are widely used as food. Two new tannins, 1 and 2, one new neolignan, 14, one new norlignan, 17, and 20 known compounds, 3-13, 15, 16, and 18-24 were isolated from T. natans pericarps in this study. The 1, 2, 14, and 17 structures were elucidated using a chemical method and extensive spectral evidence. A series of hydrolyzable tannins, 1-8, a lignin, 13, a flavonoid, 16, a norlignan, 17, and phenolic compounds, 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 43 publications
0
19
0
Order By: Relevance
“…Eight phenolic compounds (R t = 9. 45, 23.07, 24.15, 24.76, 30.72, 35.58, 36.52 and 47.65 min) were tentatively identified according to previous studies (Hatano et al 1990;Huang et al 2016). Their structures were shown in Figure 1B.…”
Section: Analysis Of Chemical Constituents and Content Of Tqpe By Hplmentioning
confidence: 65%
See 1 more Smart Citation
“…Eight phenolic compounds (R t = 9. 45, 23.07, 24.15, 24.76, 30.72, 35.58, 36.52 and 47.65 min) were tentatively identified according to previous studies (Hatano et al 1990;Huang et al 2016). Their structures were shown in Figure 1B.…”
Section: Analysis Of Chemical Constituents and Content Of Tqpe By Hplmentioning
confidence: 65%
“…But the pericarps of T. quadrispinosa were usually discarded in large quantities after the seeds had been harvested. Interestingly, recent researches have demonstrated that the pericarps of water caltrop also displayed multiple biological activities, including hypoglycemic (Huang et al 2016), anti-tumor (Lin et al 2013), anti-inflammatory (Kim et al 2015), antioxidant effects and hepatprotective activity (Kim et al 2014). To our knowledge, the therapeutic effect of Trapa quadrispinosa pericarps extract (TQPE) in high-fat diet (HFD) induced NAFLD, remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The correlation between H-1 to H-6 [δ H 5.05 (H-1), 3.46 (H-2), 3.48 (H-3), 3.37 (H-4), 3.77 (H-5), 4.23 and 4.55 (H 2 -6)] showed a coupling network in the 1 H- 1 H COSY spectrum, which proved the presence of the sugar unit to be a glucospyranoside ( Figure 4 ). The β-configuration of glucopyranose was determined through NOESY correlations and coupling constant [ 12 ]. HMBC correlations between the H-6 and carbonyl carbon (δ C 169.1, C-9″) indicated the presence of p -coumaroyl moiety at glucose methylene signal (δ C 64.7, C-6).…”
Section: Resultsmentioning
confidence: 99%
“…Its husk have higher bioactivity properties (anti-cancer, anti-atherogenic, antimicrobial, antioxidant, hepatoprotective, immune enhancing, anti-imflammatory, anti-hyperglycemic, anti-skin photoaging) than fruits (Zhu, 2016). After harvesting period, pink colored TN husks change its color to dark brown in time (Huang et al, 2016). These husks contain dietary fibres and polyphenols (such as hydrolysable tannins) (Yasuda et al, 2014;Kim et al, 2014;Huang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…After harvesting period, pink colored TN husks change its color to dark brown in time (Huang et al, 2016). These husks contain dietary fibres and polyphenols (such as hydrolysable tannins) (Yasuda et al, 2014;Kim et al, 2014;Huang et al, 2016). The total phenolic, flavonoid and tannin amounts in TN husk extract were: 63.81% mg/g gallic acid equivalents, 21.34% mg/g of rutin equivalents and 17.11% mg/g of total tannin equivalents respectively (Malviya et al, 2010;Zhu, 2016).…”
Section: Introductionmentioning
confidence: 99%